IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) BERBASIS BUDAYA MUTU ILAHIYAH DALAM MENINGKATKAN MUTU LULUSAN DI MI AT-TAQWA KOTA SAMARINDA - Akhmad Nor; Ahmad Ridani (STKIP Subang, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) based on an Ilahiyah quality culture in improving graduate quality at MI AT-TAQWA Samarinda City. The study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, teachers, educational staff, school committee members, and parents. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, while data validity was ensured through triangulation and member checking. The findings indicate that TQM was implemented through systematic and participatory planning involving all stakeholders. The values of amanah (trustworthiness), ihsan (excellence), istiqamah (consistency), and akhlaqul karimah (good character) were integrated into educational activities and school management practices. The implementation of TQM supported continuous improvement in educational processes and contributed to the development of graduates with strong academic achievement, Islamic character, and spiritual values. The study concludes that TQM based on an Ilahiyah quality culture is an effective strategy for improving graduate quality in Islamic educational institutions.